Catalytic Enantioselective Inverse-Electron-Demand Diels–Alder Reaction of 2-Pyrones and Vinyl Selenides - You, Xin-Yu; Cai, Quan (Synlett, 2023)
We report an asymmetric inverse-electron-demand Diels–Alder reaction of electron-deficient 2-pyrones with various phenyl vinyl selenides catalyzed by a chiral bis(oxazoline)/Cu(OTf)2 complex. By using a side-arm-modified chiral bis(oxazoline)ligand, a variety of [2,2,2]-bicyclic lactones with phenyl selenide substituents were obtained in good to excellent yields (up to 99%) and enantioselectivities (up to 98% ee) under mild conditions. Based on this strategy, a highly concise enantioselective synthesis of the Corey lactone was accomplished.
Keywords: asymmetric catalysis; inverse-electron-demand Diels–Alder reaction; pyrones; phenyl vinyl selenides; Corey lactone